Analysis of the Effectiveness of Islamic Religious Education in Improving the Emotional Balance of Alpha Genes in the Digital Era - Anne Salsha Bila; Anisa Dwi Makrufi (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
The rapid development of digital technology affects the character and emotional balance of Generation Alpha, who grew up as a true digital generation with high interaction intensity with digital devices. This study aims to analyze the effectiveness of Islamic Religious Education (PAI) in improving the emotional balance of Generation Alpha in the digital era. The method used is quantitative, with a survey and questionnaire on 100 7th grade students at SMP Muhammadiyah 3 Yogyakarta and data analysis using SEM-PLS through SmartPLS 4.0. The results showed that the effectiveness of PAI implementation has a positive and significant influence on the emotional balance of Generation Alpha, with a correlation coefficient of 0.981 and high significance (p<0.05). The integration of a religious approach with a digital-based adaptive learning strategy has been shown to improve emotional stability and understanding of religious values of students. In conclusion, the adaptive and integrative PAI learning model is effective in improving the emotional and spiritual balance of Generation Alpha students in the digital era, so it is important to continue to develop it to suit the psychological needs and characteristics of this generation.